Cybersecurity Awareness in Government Institutions: A Systematic Review of Behavioral Strategies and Policy Readiness - Mwansa, Gardner (Politeknik Negeri Batam, 2025)
This study presents a systematic literature review of cybersecurity awareness in government institutions, focusing on how public agencies perceive, implement, and sustain awareness initiatives. It critically examines behavioral strategies, training methods, and policy frameworks that influence employee engagement and institutional readiness. Findings highlight the fragmentation of awareness efforts, gaps in policy coordination, and the need for behaviorally informed, role-specific interventions to build cyber resilience in the public sector. Recommendations include strengthening institutional infrastructure, leadership engagement, and adaptive learning strategies to enhance cybersecurity awareness and long-term resilience.